Упростить выражение
((sin^3альфа : cos альфа) + (cos^3(-альфа) : sin (-альфа))) + 4ctg2альфа) * tg 2 альфа

1

Ответы и объяснения

2012-02-28T10:34:46+04:00

заменим альфа на x(так писать удобней)

((sin^3x/cosx+cos^3(-x)/sin(-x))+4ctg2x)*tg2x=2

1). sin^3x/cosx+cos^3(-x)/sin(-x)=sin^3/cosx-cos^3/sinx=(sin^4x-cos^4x)/sinxcosx=

-(cos^2x-sin^2x)(sin^2x+cos^2x)/sinxcosx=-2cos2x/2sinxcosx(домножили на 2)=

-2cos2x/sin2x=-2ctg2x

2). -2ctg2x+4ctg2x=2ctg2x

3). 2ctg2x*tg2x=2cos2x/sin2x*sin2x/cos2x=2